2004
DOI: 10.1890/02-0719
|View full text |Cite
|
Sign up to set email alerts
|

Relating Size of Juveniles to Survival Within and Among Populations of Chinook Salmon

Abstract: Abstract. Understanding relationships between the size of individuals and their subsequent survival can not only provide insights into mechanisms of mortality, but can also identify traits to measure for monitoring at-risk populations. We analyzed a data set of more than 54 000 juvenile chinook salmon (Oncorhynchus tshawytscha) from 15 populations over five years. The juveniles were tagged during the summer in their freshwater rearing habitats and then recaptured at downstream sites the following spring after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
155
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(170 citation statements)
references
References 42 publications
11
155
1
1
Order By: Relevance
“…Consistent with previous findings [23,29,[33][34][35], length was positively correlated with survival for nearly all year and reach combinations examined for both PIT and AT fish. One field study failed to detect a relationship between length and survival among acoustic-tagged Chinook salmon smolts emigrating through the Fraser River Basin [36].…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with previous findings [23,29,[33][34][35], length was positively correlated with survival for nearly all year and reach combinations examined for both PIT and AT fish. One field study failed to detect a relationship between length and survival among acoustic-tagged Chinook salmon smolts emigrating through the Fraser River Basin [36].…”
Section: Discussionsupporting
confidence: 91%
“…In the Columbia, linked trophic and population models have been essential in understanding the scope of predation by northern pikeminnow (Ptychocheilus oregonensis) and nonnative predators in the mainstem river reservoirs (59)(60)(61)(62), impacts of predation by gulls (Larus spp.) and Caspian terns (Hydroprogne caspia) on migrating juvenile salmon (63)(64)(65)(66), impacts of nonnative mysids and lake trout on kokanee and native salmonids in lakes (28,67), complex species interactions (68), and stage-specific growth and survival of some juvenile salmon populations during freshwater and early marine rearing (69,70). General statistical and population models have been used to explore density dependence and carrying capacities in lakeand stream-rearing populations (71)(72)(73)(74).…”
Section: Incorporating a Food Web Perspective Into Managementmentioning
confidence: 99%
“…Several recent studies of Pacific salmon Oncorhynchus spp. have shown that individuals that survive to adulthood were often larger than average as juveniles (Beamish et al 2004;Zabel and Achord 2004;Moss et al 2005;Claiborne et al 2011; Thompson and Beauchamp 2014), and growth rates during initial marine residence are often correlated with survival in both Atlantic Salmon Salmo salar and Pacific salmon (Holtby et al 1990;Jonsson et al 2003;Miller et al 2014) and marine fish in general (Sogard 1997). However, while variation in timing and size at ocean entry is well documented between species or populations occupying independent river basins (e.g., Groot and Margolis 1991;Quinn 2005;Spence and Hall 2010), far less is known about the variation among populations within basins that enter the ocean at a common location (Beamish et al 2013).…”
mentioning
confidence: 99%